Matrix converter open circuit fault diagnosis with asymmetric one zero SVM - Zhang, Jiawei; Empringham, Lee; De Lillo, Liliana; Dan, Hanbing; Wheeler, Patrick (2017)
An open-circuit fault detection and diagnosis strategy for a direct matrix converter is proposed in this paper. The current recirculating path during an open circuit condition is considered in detail with the aim of contributing more expert knowledge to the fault detection system for matrix converter. Simulation results are presented demonstrate the open circuit fault behavior of matrix converter. This expert knowledge is extremely important for the fault detection system to avoid false diagnosis. This work leads to the presentation of a reliable and fast fault detector for the Matrix Converter.